Utilization of Smart TV Technology to Support the Learning Process at SD Supriyadi 02 Semarang - Hakim, Joni Luqman; Purnamasari, Veryliana; Kartinah, Kartinah; Sofiati, Ranto Netty (JUPE : Jurnal Pendidikan Mandala, 2023)
This study aims to determine the use of Smart TV technology in supporting the learning process at SD Supriyadi 02 Semarang. Smart TV is used as a learning medium to enrich learning methods in class. The research method used was observation and interviews with one research subject, who was randomly selected. The results of the study show that the use of Smart TV can maintain students' focus and make them more enthusiastic about learning. This can be seen from the observation that students do not talk to themselves when learning takes place and do not disturb their friends who are also participating in learning in the classroom. Learners focus on the material delivered by the teacher through a smart TV, which displays learning videos about advertisements. In addition, students also become sleepy during learning because the material presented on Smart TV is attractive to them. Based on the research results, the use of Smart TV technology can be an alternative to improve the quality of learning at SD Supriyadi 02 Semarang. However, this research was only conducted on one subject, so further research is needed with a larger sample to test the effectiveness of using Smart TV as a learning medium in class